Therapeutic, Prophylactic, and Functional Use of Probiotics: A Current Perspective - Aponte, Maria; Murru, Nicoletta; Shoukat, Mahtab (Frontiers in Microbiology, 2020)
Probiotics are considered as the twenty-first century panpharmacon due to their competent remedial power to cure from gastrointestinal dysbiosis, systematic metabolic diseases, and genetic impairments up to complicated neurodegenerative disorders. They paved the way for an innovative managing of various severe diseases through palatable food products. The probiotics’ role as a “bio-therapy” increased their significance in food and medicine due to many competitive advantages over traditional treatment therapies. Their prophylactic and therapeutic potential has been assessed through hundreds of preclinical and clinical studies. In addition, the food industry employs probiotics as functional and nutraceutical ingredients to enhance the added value of food product in terms of increased health benefits. However, regardless of promising health-boosting effects, the probiotics’ efficacy still needs an in-depth understanding of systematic mechanisms and factors supporting the healthy actions.